Trypanosoma cruzi Infection and Host Lipid Metabolism - Miao, Qianqian; Ndao, Momar (Mediators of Inflammation, 2014)
Trypanosoma cruzi is the causative agent of Chagas disease. Approximately 8 million people are thought to be affected worldwide. Several players in host lipid metabolism have been implicated in T. cruzi-host interactions in recent research, including macrophages, adipocytes, low density lipoprotein (LDL), low density lipoprotein receptor (LDLR), and high density lipoprotein (HDL). All of these factors are required to maintain host lipid homeostasis and are intricately connected via several metabolic pathways. We reviewed the interaction of T. cruzi with each of the relevant host components, in order to further understand the roles of host lipid metabolism in T. cruzi infection. This review sheds light on the potential impact of T. cruzi infection on the status of host lipid homeostasis.